A pragmatic approach to Katherine Mansfield's "The man without a temperament" - Alonso Rodríguez, Pilar (Revista Alicantina de Estudios Ingleses, 1995)
Katherine Mansfield's "The Man without a Temperament" seems to encourage two opposite types of response among its readers, especially with regard to the role played by the male protagonist. Some readers reject the character with deep contempt, others admire his conduct. The co-existence of these contradictory opinions poses a reception problem. The aim of this paper is to investigate this problem from a pragmatic point of view. The analysis of the language selected and the situational constituents shows how the double response is intrinsically created by the producer's own decisions (conscious or unconscious), and how it may be interpreted as a natural consequence of the reading of the text.